Exploring the Effect of a Scaffolding Design on Students’ Argument Critique Skills - Song, Yi; Chao, Szu-Fu; Attali, Yigal (Informal Logic)

(untitled) (Informal Logic, 2020)
We designed scaffolded tasks that targeted the skill of identifying reasoning errors and conducted a study with 472 middle school students. The study results showed a small positive impact of the scaffolding on student performance on one topic, but not the other, indicating that student skills of writing critiques could be affected by the topic and argument content. Additionally, students from low-SES families did not perform as well as their peers. Student performance on the critique tasks had moderate or strong correlations with students’ state reading and writing test scores. Implications of the scaffolding and critique task design are discussed.